Structural characterization and EXAFS wavelet analysis of Yb doped ZnO by wet chemistry route - Otal, Eugenio Hernan (2015)
Lanthanide doped ZnO are interesting materials for optical and electrical applications. The wide band gap of this semiconductor makes it transparent in the visible range (Egap = 3.2 eV), allowing a sharp emission from intra shell transition from the lanthanides. From the electrical side, ZnO is a widely used material in varistors and its electrical properties can be tailored by the inclusion of lanthanides. Both applications are influenced by the location of the lanthanides, grain boundaries or lattice inclusion. Yb doped ZnO samples obtained by wet chemistry route were annealed at different temperatures and characterized by Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Rietveld refinement of XRD data, and X-ray Absorption Fine Structure (XAFS). These techniques allowed to follow the changes occurred in the matrix and the Yb environment. The use of the Cauchy continuous wavelet transform allowed identifying a second coordination shell composed of Zn atoms, supporting the observations from XRD Rietveld refinement and XAFS fittings. The information obtained confirmed the incorporation of Yb in Oh sites of the wurtzite structure without Yb2O3 clustering in the lattice.